Decreased protein C function predicts mortality in patients with cirrhosis. (28th April 2018) - Patil, A. G.; Bihari, C.; Shewade, H. D.; Nigam, N.; Sarin, S. K.
Abstract: Introduction: Protein C (PrC), a physiological anticoagulant, regulates inflammation and cell death and has known predictive/therapeutic roles in sepsis. Accumulating evidences suggest plasma hypercoagulability results in progression of fibrosis and formation of microclots causing end‐organ dysfunction. We investigated a possible association between natural anticoagulants—PrC, protein S (PrS) and antithrombin III (AT)—and clinical outcomes in cirrhotics. Methods: Functional PrC, PrS and AT were analysed in 515 cirrhotic patients and compared with 229 noncirrhotics. Among those with cirrhosis, we conducted multivariable predictive model on 3‐month survival to assess the prognostic ability of anticoagulants. Results: Protein C ( P < .001), PrS ( P < .001) and AT ( P < .001) levels were lower in cirrhotics compared with noncirrhotics. In addition, patients with Child‐Pugh (CP)‐C had significantly lower ( P < .05) functional PrC, PrS and AT levels than CP‐B, CP‐A and noncirrhotic patients. Low PrC function correlated with markers of liver dysfunction and inflammation: INR( r = −.72, P < .001), bilirubin ( r = −.620, P < .001), albumin ( r = .539, P < .001), creatinine ( r = −.417, P < .001), ferritin ( r = −.68, P = .035), procalcitonin ( r = −.79, P = .01), raised ESR ( r = .56, P < .001) and liver fibrosis ( r = −.840, P < .001). Patients who died (n = 160) had significantly lower median PrC function (23.8%, 16.3‐33.0]) compared with those who remained alive (74.9%, [59.7‐92.5]); P < .001. In a multivariable predictive model using PrC, and MELD score, we found a significant impact of low PrC levels on survival ( P < .001, IRR = 0.97, 95% CI = 0.96‐0.98). Receiver operating characteristic (ROC) curve analysis revealed that functional PrC levels <52% were associated with increased mortality ( P < .001). Conclusion: Low functional protein C level correlated with markers of liver dysfunction, inflammation and sepsis and independently predicted mortality at 3 months in cirrhotics, especially if functional levels were <52%.